The Chemical States of Color-Induced Cations in Tourmaline Characterized by X-Ray Photoelectron Spectroscopy - Ming Li; Hanlie Hong; Ke Yin; Chaowen Wang; Feng Cheng; Qian Fang (Journal of Spectroscopy)
In order to better understand the effect of transition metal cations on color of tourmaline, X-ray photoelectron spectroscopy was used to investigate the species, chemical state, site occupancy, and chemical environment of color-induced metal cations in colorful tourmaline samples from Minas Gerais State, Brazil. Our results showed that the colorful tourmalines usually contained a small amount of transition metal elements, and a colorful tourmaline sample had several transition metal cations; however, the color of tourmaline resulted from the transition metal cations in the Y site of the crystal structure. The pink color of tourmaline was associated with Mn2+ in the Y site coordinating with F; the yellow color was derived from Ni2+ in the Y site binding to O; the green color was associated with Fe3+ in the Y site coordinating with O, OH, and F; the rose red color originated from Mn2+ and Ni2+ in the Y site in which Mn2+ coordinated with O and F, and Ni2+ coordinated with O; and the blue color was derived from Fe3+ and Mn2+ in the Y site in which Fe3+ binded to O, OH, and F and Mn2+ binded to F. Additionally, other transition metal cations were also observed in colorful tourmalines, but all these species occupied the Z site of the structure. In the pink and yellow samples, Fe and Cr were observed in Fe3+ and Cr3+; in the rose red sample, Fe was also found in Fe3+; in the blue sample, Cr was present in Cr3+; in the green sample, Mn, Ni, and Cu were found in Mn2+, Ni2+, and Cu2+, respectively. The color of tourmaline was induced from the absorption of the d-d transition of transition metals in the crystal structure, as charge transfer tended to occur between cations occupying different coordination positions.